Kualitas Pelayanan Ombudsman Perwakilan Kalimantan Selatan dalam Menindaklanjuti Laporan Pengaduan Masyarakat Kota Banjarmasin - Beni Akhmad; Mita Sari (Anterior Jurnal, 2019)
This research focuses on exposure to the quality of service of the Ombudsman of the Republic of Indonesia Representative of South Kalimantan and various efforts made in following up reports on complaints from the public in Banjarmasin on administrative matters carried out by bureaucrats in public service agencies/organizations that hinder or reduce the fulfillment of excellent service for the people. The research approach used is qualitative. This study uses interview guidelines as a research instrument. Qualitatively, this study found that, based on the Gronroos service quality model, the service of the Ombudsman of the Republic of Indonesia Representative of South Kalimantan in following up public complaints reports in accordance with Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia with reference to Article 24 to Article 38, in following up on complaints from the public, the Ombudsman is impartial and able to be an effective communication facilitator between the organizer and users of public services so that each party can obtain rights and fulfill its obligations. The study found the main factor in the Ombudsman's service constraints in following up the report because of the lack of information and knowledge of the community about formal and material requirements that must be completed when submitting a complaint report. From the results of these studies, researchers recommend increasing information and knowledge about the functions, duties, and authorities of the Ombudsman by conducting socialization activities to the public, students, and public service providers.